Association Between Future Orientation and Anxiety in University Students During COVID-19 Outbreak: The Chain Mediating Role of Optimization in Primary-Secondary Control and Resilience - Chen, Yilin; Xu, Hui; Liu, Chuanshi; Zhang, Jing; Guo, Chenguang (Frontiers in Psychiatry, 2021)
The unfamiliar and menacing epidemic has undoubtedly increased the anxiety of students. Therefore, the strategies to reduce anxiety are urgently required. The present study principally investigated a protective mechanism of future orientation in anxiety during the low-risk period of COVID-19 outbreak. The study was conducted in 528 noninfected students (range = 16–24 years) recruited from five universities in China. The participants completed questionnaires between January 22, 2021, and January 24, 2021. Chain intermediary analyses were performed after controlling for gender and age. Results indicated that future orientation lowers anxiety through (a) optimization in primary and secondary control, (b) resilience, and (c) chain mediating path of optimization in primary and secondary control coupled with resilience. We investigated how individuals deal with risk factors after encountering adversity and how their psychological flexibility stimulates and promotes them to achieve a well-adapted developmental state. This study provided reference suggestions on reducing anxiety levels during an emergency.